2018
DOI: 10.3390/molecules23123372
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Rosmarinate Protects High Glucose-Induced Injury in Human Endothelial Cells

Abstract: Ethyl rosmarinate (RAE) is one of the active constituents from Clinopodium chinense (Benth.) O. Kuntze, which is used for diabetic treatment in Chinese folk medicine. In this study, we investigated the protective effect of RAE on high glucose-induced injury in endothelial cells and explored its underlying mechanisms. Our results showed that both RAE and rosmarinic acid (RA) increased cell viability, decreased the production of reactive oxygen species (ROS), and attenuated high glucose-induced endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…These results indicated that ethyl rosmarinate promoted vasorelaxation, which may be related to the increase in eNOS which then increases the response to ACh with no alteration in vascular smooth muscle cell integrity. These results are in accordance with previous studies that stated that rosmarinic acid dilated aortic rings with an endothelium-dependent pathway and prevented endothelial cell damage in high-glucose conditions [16,33].…”
Section: Discussionsupporting
confidence: 93%
“…These results indicated that ethyl rosmarinate promoted vasorelaxation, which may be related to the increase in eNOS which then increases the response to ACh with no alteration in vascular smooth muscle cell integrity. These results are in accordance with previous studies that stated that rosmarinic acid dilated aortic rings with an endothelium-dependent pathway and prevented endothelial cell damage in high-glucose conditions [16,33].…”
Section: Discussionsupporting
confidence: 93%
“…After LPS stimulation, the levels of p-p65 was increased dose dependently ( Figure 6A ). In line with the results of GPs in vivo, LPS co-treated with GPs could inhibit the expression of p-p65, just as ammonium pyrrolidinedithiocarbamate (PTDC), a widely used NF-κB pathway inhibitor 23 , 24 ( Figure 6B and C ) and the cytokines of TNF-α, IL-1β, IL-6, VCAM1 in HPMEC ( Figure 6D ), indicating GPs reduced the cytotoxicity of LPS to HPMEC.
Figure 6 GPs alleviated inflammatory response in endothelial cells.
…”
Section: Resultssupporting
confidence: 77%
“…Synapic acid derivatives exhibited antioxidant, antimicrobial, anti-inflammatory, anti-cancer, anti-anxiety (Nićiforović et al, 2017), anti-glycemic, neuroprotective, antibacterial (Chen, 2016) and analgesic activities (Hameed et al, 2016). Rosmarinic acid esters exhibited a broad spectrum of biological effects (Shen et al, 2018;Liang et al, 2017;Thammason et al, 2018). Glycerol phenylpropanoid glucosides act as hepatic glucose production inhibitors; structure-activity relationships indicated that the hydroxylation pattern of the hydroxycinnamic acid moiety and acetylation accounted for differences in activity (Murray et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectra of compounds 24 (Rt -10.3 min) and 26 (Rt -11.0 min) displayed the same [M -H]at m/z 387. The mass spectrum of compound 24 (Rt -10.3 min) exhibited base peak at m/z 163, that resulted to the loss of 225 Da from the molecular ion at m/z 387, which was formed by cleavage of the ester bond (Aziz et al, 2014;Shen et al, 2018;Wicha et al, 2015). Compound 24 was tentatively identified as ethyl rosmarinate.…”
Section: Compounds Detected By Rphplc-esi-ms/ms Analyses Of Stem Ethamentioning
confidence: 99%